Penerapan Konsep Learning Commons sebagai Upaya dalam Revitalisasi Layanan di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Effendi, Elza Melvita (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThis research aims to describe (1) the form of the application of the learning commons concept in the Archives Service and Library West Sumatra Province; (2) the concept of learning commons in the Archives and Library of West Sumatra Province; (3) efforts to realize learning commons in the Archives and Library of West Sumatra Province; and (4) factors that must be considered in applying the concept of learning commons. This study uses a descriptive method with a qualitative approach, which is collecting data by conducting observations and interviews with librarians and library users in the Archives Service and Library West Sumatra Province. The results of the research that have been carried out show, First, the form of the application of the concept of learning commons in the Archives and Library of West Sumatra Province is applied in information technology, namely by using the INLISLite application to provide technology-based services as well as maximum utilization of library space and facilities. Second, there are three concepts of learning commons that exist in the Archives and Library of West Sumatra Province, namely, the concept of learning, the concept of discussion, and the concept of information technology. Third, the efforts made in realizing learning commons in the Archives Service and Library of West Sumatra Province are influenced by the performance of librarians in the Archives and Library West Sumatra Province. Fourth, there are seven factors that must be considered in implementing the concept of learning commons, namely, user-centered, flexible, repetitive questions, join resources, delete remove barriers, trust your users, and publicize. All these factors have been carried out by the Office of Archives and Library of West Sumatra Province although there are still some applications that have not been maximized.Keywords: library; concept; learning commons.